Balance between pro-inflammatory/anti-inflammatory indicators of SOD1G93A microglia in steady conditions and modification by immunomodulation - Ezequiel, Catarina Alexandra Barbosa (2020)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017